Do capital requirements and their international differences affect banks' profitability? - Manuel Buchholz; Axel Löffler; Patrick Sigel (Deutsche Bundesbank, 2025)
A key element of the Basel III reforms are stricter capital requirements, which have been im- plemented with varying degrees of stringency across jurisdictions. We examine the impact of these requirements on bank profitability in the US and Europe between 2019 and 2024. We find no evidence that higher capital ratios or requirements negatively affect profitability. However, our results indicate that international differences in capital requirements can influence the profitability of banks that operate globally: Since capital requirements in a jurisdiction apply only to domestic banks and foreign subsidiaries, foreign banks operating through cross-border or branch-based activities may gain a competitive advantage. Nevertheless, the effect appears to be limited to the subsample of German significant institutions (SIs). Moreover, our analysis of policy scenarios based on the estimated spillover effects suggests that lowering capital requirements is not an effective strategy for improving bank profitability and could even be detrimental if reciprocated by foreign jurisdictions.
Keywords: G15; G21; G28; G32; 330; Bank capital; capital requirements; bank profitability